The first substitution reactions of N, N-spiro bridged octachlorobiscyclotriphosphazene. (25th September 2015) - Beşli, Serap; Doğan, Semih; Mutlu, Ceylan; Yuksel, Fatma
Graphical abstract: The nucleophilic substitution reaction of N, N -spiro bridged octachlorobiscyclotriphosphazene with disodium salts of ethanediol lead to formation of stable trans, cis and ipsilateral di-spiro isomers. Abstract: The reaction of the N, N -spiro bridged octachlorobiscyclotriphosphazene N3 P3 Cl4 [br-N(CH2 )5 CH3 ]2 N3 P3 Cl4 (1 ), in three (1:1 stoichiometries, 1:2 and 1:3.5), with the sodium derivative of 1, 2-ethanediol in THF solution at room temperature produced five products, the mono-spiro derivative N3 P3 Cl2 [O(CH2 )2 O][br-N(CH2 )5 CH3 ]2 N3 P3 Cl4 (2 ), cis and trans di-spiro derivatives N3 P3 Cl2 [O(CH2 )2 O][br-N(CH2 )5 CH3 ]2 [O(CH2 )2 O]N3 P3 Cl2 (3, 5 ), the ipsilateral di-spiro isomer N3 P3 [O(CH2 )2 O]2 [br-N(CH2 )5 CH3 ]2 N3 P3 Cl4 (4 ) and the tetra-spiro derivative N3 P3 [O(CH2 )2 O]2 [br-N(CH2 )5 CH3 ]2 [O(CH2 )2 O]2 N3 P3 , (6 ), whose structures have been characterized by elemental analysis, mass spectrometry, 1 H and 31 P NMR spectroscopy and X-ray crystallography. The nucleophilic substitution reactions of the N, N -spiro bridged octachlorobiscyclotriphosphazene were investigated for the first time and X-ray crystallographic studies of all the structures (2 –6 ) have been reported as the first examples of derivatives of this new class of ring system in the literature.